Filling the gap: new precise Early Cretaceous radioisotopic ages from the Andes - Aguirre Urreta, Beatriz (2015)
Fil: Aguirre Urreta, Maria B. Universidad de Buenos Aires. Instituto de Estudios Andinos Don Pablo Groeber (UBA-CONICET). Buenos Aires, Argentina.